A-Kinase Anchor Protein 4 (proAKAP4): Protein Molecule–Based Fertility Marker of Indonesian Dairy Bull and Its Correlation With Frozen-Thawed Sperm Quality - Berlin Pandapotan Pardede; Erif Maha Nugraha Setyawan; Syahruddin Said; Asmarani Kusumawati; Bambang Purwantara; Mulyoto Pangestu; Erdogan Memili (Veterinary Medicine International)
The precursor protein of A-kinase anchor protein 4 (proAKAP4), which is abundant in the fibrous sheath of sperm, plays an essential role in sperm motility and has been developed into one of the candidate molecular-based fertility markers. This study aimed to identify proAKAP4 in the sperm of Indonesian dairy bulls and to investigate its correlation with various sperm quality characteristics. The findings are expected to be applied and developed to optimize the use of superior dairy bulls. Frozen semen from 20 Indonesian dairy bulls were used, which had previously been classified based on their fertility levels into two groups: high fertility (HF) and low fertility (LF). Analysis of frozen-thawed sperm quality, such as progressive and total motility, sperm kinematics, membrane integrity, mitochondrial membrane potential, acrosome integrity, and capacitation status, was carried out in both groups. ProAKAP4 protein in frozen-thawed sperm was analyzed using the Bull 4MID Kit with the ELISA technique. Each dairy bull showed varying proAKAP4 abundance (p<0.05) from one another. Frozen-thawed sperm quality in HF bulls was higher (p<0.05) than in LF bulls, especially in total and progressive motility, sperm kinematics, membrane integrity, mitochondrial membrane potential, acrosome integrity, and noncapacitated sperm. The parameters of capacitated and acrosome-reacted sperm showed the opposite results, where the quality in LF bulls was higher (p<0.05) than in HF bulls. The results of proAKAP4 identification showed that the protein abundance in HF bulls was higher (p<0.05) than in LF bulls. Correlation analysis confirmed a strong association (p<0.05) between proAKAP4 levels and sperm fertility rate. The proAKAP4 protein has great potential to be developed and applied as a marker for determining the fertility of dairy bulls and for selecting superior dairy bulls.